IDENTIFIKASI ZONA MINERALISASI BIJIH BESI MENGGUNAKAN METODE POLARISASI TERINDUKSI DI DAERAH ULUSULITI DAN TANJUNG LIMA KAPAS, SOLOK SELATAN, SUMATRA BARAT: IDENTIFICATION OF IRON ORE MINERALIZATION ZONE USING INDUCED POLARIZATION METHOD AT ULUSULITI AND TANJUNG LIMA KAPAS AREA, SOUTHERN SOLOK, WEST SUMATRA - Bodjawati, Maharani Sarastika; Heditama, Dzil Mulki; Muttaqin, Yudi Aziz (Pusat Sumber Daya Mineral Batubara dan Panas Bumi, 2020)
The Ulusuliti and Tanjung Lima Kapas area, Koto Parik Gadang Diateh District, South Solok Regency, West Sumatra Province has a potential of iron ore form mineralization zone which is formed from the limestone formation intruded by granodiorite. Induced polarization method measurement was carried out in time domain using a dipole-dipole configuration with a space between the electrodes of 50 m. Induced polarization data was measured as many as 11 lines with a length of each line of 1.200 m and a distance between the line of 100 m to 300 m. 2D modeling was carried out to produce resistivity and chargeability sections of each line. 3D modeling was carried out to identify the distribution of the iron ore mineralization zone in the study area, both vertical and horizontal. In the 2D resistivity and chargeability model, the zone of iron ore mineralization is estimated to have a resistivity value > 500 ohm.m and a chargeability > 150 miliseconds. These values are might be iron ore minerals as a result of hydrothermal alteration formed due to the interaction between magmatic and meteoric fluids originating from granodiorite rock interacts with limestone. The result of the 3D modeling shows the continuity of the mineralized zone in a relatively southwest-northeast direction with a volume of 864.000 m3.